Endogenous Creatinine Clearance as a Clinical Measure of Glomerular Filtration Rate. Issue 5779 (9th October 1971) - Bennett, William M.; Porter, George A.
Abstract : Endogenous creatinine clearance was assessed by inulin in 91 simultaneous studies in 41 patients and proved an accurate measurement of glomerular filtration rate. For filtration rates <20 ml/min the creatinine clearance may slightly overestimate the glomerular filtration rate. Successive determinations of filtration rate by either method may vary by 20% even though the methods agree with each other. Glomerular filtration rate itself is variable, and in its clinical usage this should be recognized.